5- Dancing Around the Same Spot? Land Reform and NGOs in Zimbabwe – ! e Case of SOS Children’s Villages - Helliker, K D (African Sociological Review, 2009)
This paper discusses the rural-based operations of an international NGO in Mashonaland Central province, Zimbabwe. The aim is to highlight the contingent variation of NGO practices within deftned limits. It does this through ‘thick description’ of the NGO of focus, the SOS Children’s Village, and compares its ‘handling‘ of the transforming countryside with the re- sponse of two other NGOs. It concludes by suggesting some conceptual points in understanding organizational dispositions of NGOs.